Development of mobile-learning media on Basic Electricity and Electronics Subject - Sumiati, Mery; Rizal, Fahmi; Anwar, Muhammad (Jurnal Pendidikan Teknologi Kejuruan, 2020)
In the learning process of basic electricity and electronics subject, students face problems in understanding the material because it is considered as difficult without supported of adequate media. Then, the time allocation for basic electricity and electronics learning in the classroom is only four hours in a week, thus the material delivering is considered as not optimally to students. Therefore, teaching learning process needs to be supported by suitable and adequate media. The purpose of this research is mobile based learning media that is valid, practical and effective for Basic Electricity and Electronics subjects. The method of this research is Research and Development (R&D). This research and development used the Borg and Gall model that consists of several stages. The instrument used in this research is validation questionnaire that was given to material experts and media experts. The results obtained from this development research are a learning media based on mobile learning in the Basic Electricity and Electronics subjects. Based on research developed media are valid media, with the results of media validation of 0.84 and material validation of 0.74. The practical value of the results of the teacher's response of 94% and student responses of 84.24% were categorized very practical. From the posttest scores students get effective results that is 0.00 which is smaller than 0.005 which means that it is significant from the value of the experimental class and the control class.